PENERAPAN FUZZY LOGIC UNTUK MEMPREDIKSI PENJUALAN MAKANAN DI USAHA SHAKEEL KEBAB MENGGUNAKAN METODE MAMDANI - Nasaruddin, Andira; Maslan, Andi (LPPM Universitas Putera Batam, 2025)
Particularly in the food industry, like Shakeel Kebab MSME, sales are a crucial performance metric. The lack of a data-driven method to predict future sales trends is one of the main issues. Using historical sales data from 2022 to 2024, this analysis predicts food sales using the Mamdani fuzzy logic method. Fuzzification, rule formation, inference, and defuzzification are all steps in the research process, and MATLAB software is used for implementation. The outcomes show that the fuzzy system can correctly identify sales trends. For example, the system generated a defuzzification value of 91.67 in September 2024, and consistently 80 in November and December. These outcomes demonstrate that the Mamdani fuzzy method is effective in supporting predictive decision-making for food sales, especially for small business owners.